Preceptors training need assessment for medical laboratory professional clinical education programs in Ethiopia - Abebe Edao Negesso; Gizachew Kedida Rikitu; Gelila Biresaw Sime; Endale H. Gebregzabher; Saba Gebremichael Tekele; Abay Sisay Misganaw (PLoS ONE, 2022)
Background Health Workforce Improvement Program and professional associations recognized the need for a formalized method of providing academic education that would improve how preceptors teach and assess student. Thus, this study aimed to assess training needs of preceptors for Medical Laboratory Science clinical practicum education programs in Ethiopia. Methods A cross-sectional survey design was implemented in targeted health facility throughout the country to assess academic educational needs of preceptors for Medical Laboratory clinical practicum education programs. The study participants were conveniently selected practicing health professionals who formally or informally nominated as a clinical trainer or acts as clinical trainer giving practical training to the student in the targeted practice setting. An adapted structured questionnaire modified to local context was used to conduct the survey and the perceived competency assessment used five scale of measurement (Not capable, Beginner, Advanced beginner, Competent, Proficient). The frequency was presented using tables and figures. Results A total of 304 laboratory professionals participated in this study. More than half (52.6%) of the study participants were in the age group of 21 to 30 years and 264/304 (86.8%) were male. The majority (43.0%) of study participants had 6 to 10 years of experience and 212 (68.8%) did not receive clinical teaching skills training in the past two years. Regarding applying different hands-on teaching methods, the majority 38/304(12.5%) were not capable for role play and community based training, 49/304(16.1%) reported being Beginners, 85/304 (28%) said that they are advanced beginners in the competency. In this study, most study participants 98/304(32.2%) and 130/304(42.8%) perceived that they are competent and proficient in applying laboratory practice teaching methods respectively. Conclusion The average cumulative level of competency from level 1 (not capable) to level 3 (advanced beginner), we found: learning in the practical teaching area 45.4%, clinical practicum teaching quality improvement and advocacy 42.9%, student assessment methods 42.7%, communication, collaboration and partnership 40.9%. Overall competence of preceptors (proportion of preceptors reported competent) was 57%. We recommend designing the performance interventions in the form of training by including communication skills for effective preceptor ship, students assessment and feedback, teaching and instruction strategies, planning for clinical practicum learning and principles of learning and teaching in practical areas.